Effect of probiotics on prognosis in patients with hepatectomy: a systematic review and meta-analysis of randomized controlled trial - Qinghu Jiang; Hua Zou; Furui Zhong; Jian Ma (BMC Pharmacology and Toxicology)
Abstract Objective To investigate the effect of perioperative probiotics on prognosis in patients with hepatectomy. Method By conducting a computer-based search of electronic databases to collect randomized controlled trials (RCTs) on the use of probiotics in the perioperative period for patients undergoing liver resection. Two researchers independently screened the literature, extracted data, assessed bias risk, and performed a meta-analysis using RevMan 5.4 software. Result A total of 988 patients were enrolled across 14 studies. The results of the meta-analysis revealed that the probiotics group had lower rates of postoperative infectious complications (OR = 0.49; 95%CI 0.49 to 0.60; P < 0.01), serum endotoxin levels (SMD= -0.69; 95%CI -1.27 to -0.11; P = 0.02), white blood cell counts (SMD= -0.37; 95%CI -0.67 to -0.061.47; P = 0.02), hospital stays (SMD= -0.85; 95%CI -1.53 to -0.18; P = 0.01), and first postoperative exhaust times (SMD= -0.85; 95%CI -1.53 to -0.18; P = 0.01) compared to the control group. No significant differences in liver function indices (alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBiL) and international normalized ratio (INR)) or postoperative inflammatory markers (C-reactive protein (CRP), procalcitonin, interleukin-6 (IL-6)) were found between the two groups (all P > 0.05). Conclusions Probiotics used perioperatively can lower postoperative infection risk and shorten hospital stays for hepatectomy patients, but they do not appear to aid in liver function restoration or inflammation reduction. Clinical trial number Not applicable.